HADIS TENTANG MENJAGA LIMA PERKARA SEBELUM DATANG LIMA PERKARA YANG LAIN (AL-HAKIM) - Istikhori Muslim; Andika Gumelar; Fatchi Mohammad Alfi Salim; Eni Nuraeni; Siti Sarifah; Saeful Bahri Alamsyah Putra (STKIP Subang, 2026)
This study examines the relevance of the hadith narrated by Al-Hakim concerning the command to safeguard five matters before the arrival of five other matters as a foundational framework for character education and life management in contemporary society. The problem addressed in this research is the declining awareness among individuals, particularly students, in optimizing time, health, youth, wealth, and life as moral and spiritual capital. The purpose of this study is to analyze the conceptual meaning of the hadith and its implications for personal responsibility, ethical development, and educational practice. This research employs a qualitative approach using library research methodology, with data sources consisting of classical hadith compilations, scholarly commentaries, and relevant educational literature. Data were analyzed through descriptive-analytical techniques to interpret the moral messages and contextual relevance of the hadith. The results indicate that the hadith provides a comprehensive ethical framework that encourages proactive behavior, self-discipline, and future-oriented thinking. It emphasizes the importance of utilizing opportunities before they are lost and aligns closely with the goals of character education, particularly in fostering responsibility, gratitude, and awareness of time. The study concludes that this hadith is highly relevant as a moral and educational guideline and can be effectively integrated into educational curricula and character-building programs to strengthen students’ spiritual and social awareness.